2018
DOI: 10.18632/oncotarget.25132
|View full text |Cite
|
Sign up to set email alerts
|

Anti-podocalyxin antibody exerts antitumor effects via antibody-dependent cellular cytotoxicity in mouse xenograft models of oral squamous cell carcinoma

Abstract: Podocalyxin (PODXL) overexpression is associated with progression, metastasis, and poor outcomes in cancers. We recently produced the novel anti-PODXL monoclonal antibody (mAb) PcMab-47 (IgG1, kappa). Herein, we engineered PcMab-47 into 47-mG2a, a mouse IgG2a-type mAb, to add antibody-dependent cellular cytotoxicity (ADCC). We further developed 47-mG2a-f, a core fucose-deficient type of 47-mG2a to augment its ADCC. Immunohistochemical analysis of oral cancer tissues using PcMab-47 and 47-mG2a revealed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 54 publications
3
40
0
Order By: Relevance
“…However, EMab-17 could not inhibit or diminish the presence of all CRC cells in the liver. As previously reported by this and other research groups, afucosylation of the Fc domain to increase the ADCC, and/or the combination of EMab-17 with anti-cancer drugs, are needed to enhance the anti-metastatic activity of EMab-17 [ 36 , 37 , 38 , 39 ]. In future studies, we need to generate a human/mouse chimeric anti-EGFR antibody from EMab-17 in order to develop the therapeutic antibody.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, EMab-17 could not inhibit or diminish the presence of all CRC cells in the liver. As previously reported by this and other research groups, afucosylation of the Fc domain to increase the ADCC, and/or the combination of EMab-17 with anti-cancer drugs, are needed to enhance the anti-metastatic activity of EMab-17 [ 36 , 37 , 38 , 39 ]. In future studies, we need to generate a human/mouse chimeric anti-EGFR antibody from EMab-17 in order to develop the therapeutic antibody.…”
Section: Discussionmentioning
confidence: 93%
“…Additional antibodies were injected on days 7 and 14. The tumor diameter and volume were determined as previously described [ 38 ]. The mice were euthanized 21 days after cell implantation.…”
Section: Methodsmentioning
confidence: 99%
“…High expression of miR-509-3-5p and miR-5100 inhibited the invasion and metastasis of gastric cancers and pancreatic cancers by directly targeting PODXL, functioning as a tumor suppressor [27,40]. A core fucose-deficient monoclonal antibody (mAb) of PODXL might be a new antibody-based therapy method against PODXL high-expressed oral squamous cell carcinoma [47].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we established specific and sensitive anti-PODXL mAbs: PcMab-47 (mouse IgG 1 , kappa) [20] , 47-mG 2a (mouse IgG 2a -type of PcMab-47), and 47-mG 2a -f (core fucose-deficient type of 47-mG 2a ) [21] . We demonstrated that 47-mG 2a -f significantly reduced tumor growth in OSCC xenograft models.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that 47-mG 2a -f significantly reduced tumor growth in OSCC xenograft models. [21] . To investigate the function of PODXL in the growth of oral cancer cells, we previously generated PODXL-knock out (PODXL-KO) cell lines using SAS OSCC cell lines.…”
Section: Introductionmentioning
confidence: 99%